Penguatan Kapasitas Perencanaan Desa Melalui Sosialisasi Pengembangan Desa Berbasis Data di Negeri Ureng - Hertine Megiestri Kesaulya; Wa Ode Sitti Jurianti Aswad; Risal Rasyid; Fienkan Laura Sandyego Dumalang (EMPOWERMENT: Journal of Community Practice, 2025)
Villages face unique challenges in the development process, particularly in the availability and management of data that serves as the foundation for planning. In Negeri Ureng, limited digital literacy and inadequate ICT infrastructure are major obstacles to realizing data-driven planning. This Community Service (PKM) activity aims to strengthen village planning capacity through the socialization of data-based village development. The method used is a qualitative and participatory approach, involving field observations, interviews with government representatives of Negeri Ureng, material delivery, and participatory evaluation. The activity was carried out in three stages: preparation, implementation of the socialization, and evaluation and follow-up. The analytical technique employed was qualitative descriptive analysis of data obtained from observations, interviews, and discussions conducted throughout the activity, focusing on identifying challenges and obstacles in the use of village data. The results show an increased understanding among village officials of the importance of data in supporting well-directed, transparent, and sustainable village development. The government of Negeri Ureng demonstrated its commitment to initiating a digital data collection process and to establishing a village data team as a first step in developing a village information system